PENINGKATAN KETERAMPILAN IBU-IBU POS YANDU MAWAR MERAH RT 50 KELURAHAN MANGGAR: PELATIHAN PEMBUATAN KUE TAKOYAKI BERNILAI EKONOMI - Misna Ariani; Tutik yuliani; Imam Ariwibowo; Dwinda Tamara (Fakultas Ekonomi Universitas Balikpapan, 2022)
The training on making Takoyaki cakes was warmly welcomed by the participants, mostly housewives who are members of the RT 50 Mawar Merah Yandu Post in Manggar Village. This training activity aims to improve the skills of participants in making Takoyaki cakes. Takoyaki cakes are nutritious and have economic value. It is easy to make and the ingredients are easily available in supermarkets. With effective discussion and hands-on practice, participants were able to make Takoyaki cake with a brownish yellow color that was nutritious and delicious. If the ability of these participants continues to become entrepreneurs, of course, they can increase additional family income. This training activity has succeeded in increasing skills and understanding that Takoyaki cake can be an alternative to additional business.